2017
DOI: 10.1111/plb.12656
|View full text |Cite
|
Sign up to set email alerts
|

Temperatures during flower bud development affect pollen germination, self‐incompatibility reaction and early fruit development of clementine (Citrus clementina Hort. ex Tan.)

Abstract: One of the key environmental factors affecting plant reproductive systems is temperature. Characterising such effects is especially relevant for some commercially important genera such as Citrus. In this genus, failure of fertilisation results in parthenocarpic fruit development and seedlessness, which is a much-prized character. Here, we characterise the effects of temperature on flower and ovary development, and on pollen-pistil interactions in 'Comune' clementine (Citrus clementina Hort. ex Tan.). We examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…Temperature stress induces different alterations to plant reproductive system physiology and phenology, including changes in flowering initiation (De Storme & Geelen, ). In citrus, temperature stress has been demonstrated to be effective in affecting pollen germination, self‐incompatibility reactions and early fruit development (Distefano et al, ). In the current study, focused on clementine, one of the most important citrus species, we monitored the effect of three temperatures in the pollen development process.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Temperature stress induces different alterations to plant reproductive system physiology and phenology, including changes in flowering initiation (De Storme & Geelen, ). In citrus, temperature stress has been demonstrated to be effective in affecting pollen germination, self‐incompatibility reactions and early fruit development (Distefano et al, ). In the current study, focused on clementine, one of the most important citrus species, we monitored the effect of three temperatures in the pollen development process.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, focused on clementine, one of the most important citrus species, we monitored the effect of three temperatures in the pollen development process. We observed that low temperature (15°C) resulted in slower growth of the flower buds starting at the young microspore stage (Stage C in Figure ), which is in accordance with our previous results (Distefano et al, ). The flower exposure to higher temperatures resulted in earlier anthesis and flower maturation without any evidence of flower functionality alterations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations